Virus infection and vesicle trafficking - Cao, Guo-Xiu; Liu, Fan-Xin; Meng, Chun-Chun; Ding, Chan; Dai, Jun; Qiu, Xu-Sheng (Frontiers in Immunology, 2025)
Vesicle trafficking mechanisms play indispensable roles throughout the viral replication cycle, though their stage-specific regulatory mechanisms during infection require further elucidation. Notably, the latest research reveals that diverse viruses strategically exploit host vesicle trafficking proteins to orchestrate critical infection phases, including receptor-mediated endocytosis initiation, viral attachment/membrane fusion, intracellular component transport, genome replication complex reorganization, and viral assembly/budding. By commandeering these trafficking pathways, viruses not only optimize cellular entry efficiency and immune evasion capabilities but also establish dynamic organelle microenvironments conducive to genome replication. Consequently, therapeutic strategies targeting vesicular transport nodes—through functional inhibition of trafficking proteins or disruption of vesicle homeostasis—have emerged as promising antiviral approaches with clinical translation potential. This review systematically examines viral phase-dependent mechanisms of host vesicular networks, elucidates infection optimization through transport pathway subversion, and evaluates current efforts in developing vesicle-targeted antivirals, thereby providing conceptual frameworks for novel therapeutic design.